The role of regional anaesthesia and multimodal analgesia in the prevention of chronic postoperative pain: a narrative review - Chen, Y.‐Y. K.; Boden, K. A.; Schreiber, K. L. (Anaesthesia, 2021)
Summary Effective prevention of chronic postoperative pain is an important clinical goal, informed by a growing body of studies. Peri‐operative regional anaesthesia remains one of the most important tools in the multimodal analgesic toolbox, blocking injury‐induced activation and sensitisation of both the peripheral and central nervous system. We review the definition and taxonomy of chronic postoperative pain, its mechanistic basis and the most recent evidence for the preventative potential of multimodal analgesia, with a special focus on regional anaesthesia. While regional anaesthesia targets several important aspects of the mechanistic pathway leading to chronic postoperative pain, evidence for its efficacy is still mixed, possibly owing to the heterogeneity of risk profiles within the surgical patient, but also to variation in techniques and medications reported in the literature.